Pilot of a Community Health Worker Video Intervention for Immigrant Day Laborers at Occupational Health Risk - Lara, Marielena; Díaz Fuentes, Claudia; Calderón, Jorge; Geschwind, Sandy; Tarver, Meshawn; Han, Bing (Frontiers in Public Health, 2021)
Significance: Immigrant day laborers suffer from disproportionate occupational health risks from hazardous reconstruction jobs after natural disasters. Methods: We conducted a randomized controlled trial of a short-video educational intervention to improve safety knowledge and intent to engage in safety preventive behaviors among 98 Hispanic day laborers (49 randomized to video and 49 control). The short video featured a male promotor and a female promotora who narrated 3 stories of day laborers who were injured while doing construction work in post-Katrina New Orleans. The main outcome measures were changes in scores for day laborer-reported safety knowledge and safety behaviors derived from interviewer-delivered baseline and post-intervention surveys. Results: Video participants reported improvement in overall average safety knowledge score (mean score of 11.3 out of a max score of 12 or 94% when standardized to 0–100% scale), as compared to the control group (mean score of 8.6 or 72%) who were not offered the video (p < 0.00001). The intervention was highly successful in workers stating that they learned and were willing to change their safety preventive behaviors to reduce their occupational risk. The average safety behavior score was higher among those watching the video (17.2 out of a max of 22 or 78.1% when standardized on a scale 0–100%) as compared to control (14.5 or 65.9%) (p = 0.0024). Conclusion: A short video intervention can improve knowledge and intent to engage in preventive behaviors among Hispanic workers for which there is a dearth of construction safety preventive research.